PENGARUH PIJAT BAYI TERHADAP KENAIKAN BERAT BADAN PADA BBLR DI RSUD TAMAN HUSADA BONTANG - Aprianing Indri Astuti; Umi Kalsum; Andi Lis Arming Gandini (Bajang Institute, 2023)
Background: LBW babies require special care because they experience various disorders such as body temperature instability, respiratory problems, immunological immaturity, gastrointestinal problems, nutrition, liver immaturity, and hypoglycemia. Premature babies are exposed to stressful environments, high-intensity noise, and continuous bright light. They lose the mechanical sensory stimulation they received in the womb. Massage can help facilitate the weight gain process. Objective: To identify the effect of baby massage on LBW weight gain in the Neonatology room at Taman Husada Bontang Regional Hospital. Method: This research is quantitative research with a quasi-experimental research design or also called quasi experiment. Pretest-Posttest with Control Group Design. The population in this study was LBW who were treated in the Neonatology room at Bontang Regional Hospital. Based on data obtained in January, the number of LBW babies was 16 babies, in February there were 10 babies, while in March there were 16 babies. If added up, there are 42 babies and on average every month around 13 babies are treated in the Neonatology room. This analysis was carried out using a paired t-test to see whether there was an effect of baby massage on increasing the baby's weight and body length. Results: The results of the study showed that the difference in the average increase in baby weight in the intervention group was 126.19 and in the control group was 37.62. The average difference in body weight between the intervention group and the control group was 163,810 and the difference was 101,545 to 226,074. The results of the independent t test obtained a Sig value. (2-tailed) is 0.000 < 0.05, then as is the basis for decision making in the independent t test, it can be concluded that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of baby massage on LBW weight gain in the NICU room at Taman Husada Bontang Regional Hospital. Conclusion: There is an effect of giving baby massage 3 x 15 minutes for 10 days on increasing the weight of LBW neonates (p=0.000).